Genetics of ncHH: from a peculiar inheritance of a novel GNRHR mutation to a comprehensive review of the literature. (21st December 2018) - Cioppi, F.; Riera‐Escamilla, A.; Manilall, A.; Guarducci, E.; Todisco, T.; Corona, G.; Colombo, F.; Bonomi, M.; Flanagan, C. A.; Krausz, C.
Abstract: Background: Normosmic congenital hypogonadotropic hypogonadism (ncHH) is caused by the deficient production, secretion, or action of gonadotropin‐releasing hormone (GnRH). Its typical clinical manifestation is delayed puberty and azoospermia. Homozygous and compound heterozygous mutations in the GNRHR gene (4q13.2) are the most frequent genetic causes of ncHH. Objectives: (i) Characterization at the molecular level (genetic origin and functional effect) of a unique homozygous mutation (p.Gly99Glu) in a ncHH man; (ii) to provide a comprehensive catalog of GNRHR mutations with genotype–phenotype correlation and comparison of in vitro studies vs. in silico prediction tools. Material and Methods: A ncHH man and his parents, in whom we performed the following: (i) Sanger sequencing, qPCR of the GNRHR gene; (ii) chromosome 4 SNP array; and (iii) competition binding assay and inositol phosphate signaling assay. PubMed and Human Genome Mutation Database (HGMD) search for GNRHR mutations. Bioinformatic analysis of 55 reported variants. Results: qPCR showed two GNRHR copies in the index case. SNP array revealed the inheritance of two homologous chromosomes 4 from the mother (maternal heterodisomy; hUPD) with two loss of heterozygosity regions, one of them containing the mutated gene (maternal isodisomy; iUPD). Functional studies for the p.Gly99Glu mutation demonstrated a right‐shifted GnRH‐stimulated signaling response. Bioinformatic tools show that commonly used in silico tools are poor predictors of the function of ncHH‐associated GNRHR variants. Discussion: Functional analysis of the p.Gly99Glu mutation is consistent with severely decreased GnRH binding affinity (a severe partial loss‐of‐function mutation). Complete LOF variants are associated with severe and severe/moderate phenotype, whereas partial LOF variants show wide range of clinical manifestations. Conclusion: This is the first ncHH patient carrying a novel causative missense mutation of GNRHR with proven 'severe pLOF' due to maternal hUPD/iUPD of chromosome 4. Our literature review shows that functional studies remain essential both for diagnostic and potential therapeutic purposes.